Paham Keagamaan K.H. Muhammad Zein bin Abdul Rauf (Kajian Filologis Naskah Kitab Kurratu Al-Ain Al- Fard Al-Ain) - Rasidin, Rasidin (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2007)
This Article aim to analyse idea of K. H. Muhammad Zein Abdul Rauf. In his article he studies three religion main problems namely tauhid, science, bahavior and.fiqh. In the feld of tauhid science he studies the nature of obligation which is called wajib, mustahil (impossible) and have to Allah SLVT. So also to nature of which is obligecl to be, irnposible and have to be for rasul, religion foundation and meaning it the two confessions. In the feld of fiqih he studies aboul taharah, fasting and sholat. While in the feld of behavior he studies about immoral related to organ which is zahir (organ irnrnoral lahiriah) and wich is mind (batiniah) and also the nature of the nature the praised attributed attached to all mukallaf.